Physicochemical features of the effect of special water-based fire retardants on forest materials; Fire Safety Journal; Vol. 123 - Kuznetsov G. V. Geny Vladimirovich; Islamova A. G. Anastasiya Gomilievna; Orlova E. G. Evgeniya Georgievna; Strizhak P. A. Pavel Alexandrovich; Feoktistov D. V. Dmitriy Vladimirovich (2021, 2021)
Title screen